Spanish Unemployment: The End of the Wild Ride? - Samuel Bentolila; Juan F. Jimeno (Center for Economic Studies and ifo Institute (CESifo), 2003)
Over the last quarter century, the Spanish unemployment rate has gone from 3.5 per cent to 24 per cent of the labor force, and then back to 13 per cent. In this paper we describe this extraordinary evolution more in detail, discuss the main shocks and institutions behind it, and provide a set of policy implications derived from our analysis.
Keywords: 330